When, where, and why should we look for vestibular dysfunction in people with diabetes mellitus? - DiLiberto, Frank E.; Kamath, Heather E. R.; Olson, Maxine L.; Cherchi, Marcello; Helminski, Janet O.; Schubert, Michael C. (Frontiers in Rehabilitation Sciences, 2024)
The biochemistry of diabetes mellitus results in multi-system tissue compromise that reduces functional mobility and interferes with disease management. Sensory system compromise, such as peripheral neuropathy and retinopathy, are specific examples of tissue compromise detrimental to functional mobility. There is lack of clarity regarding if, when, and where parallel changes in the peripheral vestibular system, an additional essential sensory system for functional mobility, occur as a result of diabetes. Given the systemic nature of diabetes and the plasticity of the vestibular system, there is even less clarity regarding if potential vestibular system changes impact functional mobility in a meaningful fashion. This commentary will provide insight as to when we should employ diagnostic vestibular function tests in people with diabetes, where in the periphery we should look, and why testing may or may not matter. The commentary concludes with recommendations for future research and clinical care.